Elucidation of copper environment in a Cu–Cr–Fe oxide catalyst through in situ high-resolution XANES investigation. Issue 10 (4th March 2021) - Lais, Tahmin; Lukashuk, Liliana; van de Water, Leon; Hyde, Timothy I.; Aramini, Matteo; Sankar, Gopinathan
Abstract : Local structure of copper ions in Cu–Cr–Fe mixed metal oxide revealed through in situ high-resolution XANES investigation. Abstract : Copper containing materials are widely used in a range of catalytic applications. Here, we report the use of Cu K-edge high resolution XANES to determine the local site symmetry of copper ions during the thermal treatment of a Cu–Cr–Fe oxide catalyst. We exploited the Cu K-edge XANES spectral features, in particular the correlation between area under the pre-edge peak and its position to determine the local environment of Cu 2+ ions. The information gained from this investigation rules out the presence of Cu 2+ ions in a tetrahedral or square planar geometry, a mixture of these sites, or in a reduced oxidation state. Evidence is presented that the Cu 2+ ions in the Cu–Cr–Fe oxide system are present in a distorted octahedral environment.